Studi in Silico Senyawa Aktif Rimpang Jahe (Zingiberis Officinalis Rhizoma) sebagai Antikanker Payudara terhadap Progesterone Receptor - Shafa Shaomi Maharani; Ratnadani Amalia Safitri; Khalisa Wahidani Aufhanggi; Amira Hasna Azis; Sasha Nurhalisa (Jurnal Kesehatan Amanah, 2025)
Breast cancer is one of the highest causes of death worldwide. Breast cancer is a malignant tumor that attacks the breast tissue which consists of the mammary glands (milk-making glands), glandular ducts (milk ducts), and breast supporting tissues. This study aims to look at the interaction of ginger compounds against progesterone receptors as anticancer of the breast. This research method includes Lipinski prediction, admetox prediction, pharmacophore screening, and molecular docking. Lipinski's prediction results show that of the 15 compounds tested, only 13 compounds were obtained that fulfilled the Lipinski rule. Admethox prediction results showed that the compounds with the best HIA, CaCO2, PPB, and BBB values were Zingiberene, beta-carotene, and Zingiberenol. The pharmacophore screening results showed model 8 as the best model with an AUC value of 100%, namely 0.71. From the results of molecular docking, it was found that Zingiberenol compound is the best drug candidate with the lowest binding energy value and KI value, namely -8.38 kcal/mol and 4.36 uM with van der waals bonds that occur in the Phe778 amino acid residue.